2021
DOI: 10.1177/23743735211039313
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Patients on Natural Herbal Treatments for Diabetes Mellitus at the Diabetes Clinic in Base Hospital - Matara, Sri Lanka

Abstract: The prevalence of diabetes mellitus has become a global public health issue. Natural herbal treatments for type 2 diabetes mellitus have been widely used in traditional societies but has recently become popular among western societies as well. The aim of this study was to explore the experience of type 2 patients with diabetes mellitus who are currently on natural herbal treatment. A qualitative, phenomenological design has been used. Twelve participants from both males and females, aged between 25 and 75 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…With regard to practice and product use, we identified that herbal medicine use was more likely for those with a mental health co-morbidity compared to those with diabetes alone. Previous research has revealed people living with diabetes [ 39 , 40 ] or depression or anxiety are high users of herbal medicines [ 41 ]. Our results indicate that the presence of either depression or anxiety is influencing herbal medicine use more so than the presence of diabetes [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to practice and product use, we identified that herbal medicine use was more likely for those with a mental health co-morbidity compared to those with diabetes alone. Previous research has revealed people living with diabetes [ 39 , 40 ] or depression or anxiety are high users of herbal medicines [ 41 ]. Our results indicate that the presence of either depression or anxiety is influencing herbal medicine use more so than the presence of diabetes [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mean (± SD) age of patients was 49.1 (10.2) and 50.9 (12.7) years in the placebo and J.regia groups, respectively. The mean duration [IQR] of their disease was 6 [4][5][6][7][8] and 6 [4][5][6][7][8] years in the placebo and J.regia groups, respectively. Patients' characteristic data were summarized in Table 1, and there was no significant difference between them (P > 0.05).…”
Section: Clinical Phasementioning
confidence: 99%
“…Recently, there has been an increase in the use of traditional medicine and herbal products for treating diabetes because they are believed to have comparable or superior therapeutic effectiveness with minimal adverse reactions. 7 Furthermore, numerous conventional remedies for diabetes are sourced from botanical substances. For instance, the first-line treatment of diabetes is metformin, which has its discovery history rooted in a herbal product ( Galega officinalis ), and its potential benefits are still being researched, in addition to lowering blood glucose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations